OP0215 Role of inhibitory igg fc receptor iib on b cells and monocytes in yaa-related murine lupus. (15th June 2017) - Hirose, S; Qingshun, L; Ohtsuji, M; Nishimura, H; Amano, H; Verbeek, SJ
Abstract : Background: FcγRIIB-deficient C57BL/6 (B6) mice spontaneously develop severe lupus nephritis in combination with Yaa locus (TLR7-duplication). Objectives: The aim of this study is to clarify the cell type-specific roles of FcγRIIB for the pathogenesis of Yaa -related lupus. Methods: We established B cell-specific (CD19 Cre . Yaa ), myeloid-derived cell-specific (C/EBPα Cre . Yaa ), and dendritic cell (DC)-specific (CD11c Cre . Yaa ) FcγRIIB-deficient mice on B6. Yaa background, and compared the disease features of these mice with full FcγRIIB-deficient B6.FcγRIIB -/- . Yaa mice. Results: CD19 Cre . Yaa mice developed milder lupus nephritis compared to B6.FcγRIIb -/- . Yaa mice, indicating that FcγRIIB deficiency on only B cells is not sufficient for the development of severe disease. Surprisingly, C/EBPα Cre . Yaa mice developed similar mild disease as CD19 Cre . Yaa mice whereas CD11c Cre . Yaa stayed disease free. These observations indicate that, in B6. FcγRIIB -/- . Yaa mice, FcγRIIB deficiency on both B cells and myeloid cells, but not on DCs, contribute to the development of severe lupus with high autoantibody titers. Flow cytometric analysis showed that the frequency of peripheral Gr-1 -, but not Gr-1 +, monocytes was increased and correlated positively with the frequency of splenic PNA + activated B cells in B6.FcγRIIB -/- . Yaa and C/EBPa Cre . Yaa, but not CD19 Cre . Yaa, mice. This suggests a link between FcγRIIB deficiency on monocytes, the high frequency of Gr-1 - monocytes and B cell activation. Transcriptome analysis of Gr-1 + and Gr-1 - monocytes revealed that B cell-stimulating factor-3 (BSF-3), IL-10, and IL-1β were all up-regulated in Gr-1 - monocytes. Conclusions: FcγRIIB on B cells and monocytes controls B cell activation and autoimmune responses via different but synergistic pathways in Yaa -related lupus nephritis. References: Boross P, et al. J. Immunol. 187:1304–1313, 2011. Disclosure of Interest: None declared